THE ROLE OF SOCIAL AND PERSONAL INSURANCE IN PROVIDING PUBLIC WELFARE IN UKRAINE - KRUPKA, Mykhailo; PRYIMAK, Iryna; VYSHYVANA, Bohdana (Scientific journal «World of Finance», 2020)
Introduction. Achieving public welfare is impossible without an effective social protection system, which combines pension insurance, social insurance, health care, as well as material support in difficult life situations. Low budget funding for social protection of population necessitates the use of insurance instruments to neutralize major social risks. However, the role of social and personal insurance in the financial provision of social protection remains insufficient, and its potential in improving the welfare of Ukrainians is underestimated. However, the role of social and personal insurance in the financial provision of social protection remains insufficient, and its potential in improving the welfare of Ukrainians is underestimated.The purpose is to define the role and outline the prospects for the development of social and personal insurance in the context of ensuring public welfare in Ukraine.Results. The essence and main components of social welfare are revealed. It was found that the level of well-being of Ukrainians is ten times lower than in European countries. There are the main negative factors which influence the social protection system defined, in particular: low income and rising expenditures of the Pension Fund of Ukraine and the Social Insurance Fund of Ukraine, the widespread practice of minimizing SSPs by refusing to enter into classic employment contracts in favor of civil agreements with individual entrepreneurs, reduction of the number of insured persons working for hire, high level of labor emigration of Ukrainians. The health care system impact on the growth of public welfare in Ukraine is analyzed. The inefficiency of the current financial support model of the health care system is substantiated, which makes it necessary for households to pay for most of the cost of medical services. Tendencies in the development of the domestic health insurance market are highlighted.Perspectives. It is proposed to revise the principles of building accumulative pension insurance and introduce a budget-insurance model of financing the health care system, which will help to improve the welfare of the population of Ukraine.